Chapter 3 American Anchor Artists and Festivals - Calamoneri, Tanya (Taylor & Francis, 2022)
"American Anchor Artists and Festivals" highlights three key artists: Maureen Fleming, Joan Laage, and Diego Piñón. All have spent numerous years in Japan and worked with the Ohnos, and two have worked with Min Tanaka. Their teaching and performance is the foundation of American butoh. Additionally, Brechin Flournoy launched the San Francisco Butoh Festival launched in 1993, the first major American festival dedicated to butoh, which developed student communities, educated critics and audiences, and cultivated the funding community to support butoh in the Americas.